Analysis of Organizational Management Diversity in the Management of Hili Cafe and Copa Cafe - Fanahadodo Dakhi, Petrus; Lase, Heseziduhu; Ndraha, Ayler Beniah; Waruwu, Eliyunus (Dinasti Publisher, 2024)
This study aims to analyze the diversity of organizational management at Hili Café and Copa Café in Gunungsitoli City. Diversity in organizations includes various individual characteristics such as ability, tenure, education, communication style, and personality. This research uses a descriptive qualitative approach with data collection methods through observation, interviews, and documentation. The results showed that the diversity of the workforce in both cafes had a positive impact in improving communication and cooperation between employees. However, there are some obstacles such as salary differences between old and new employees, the tendency of employees to associate with people from the same area of origin, and a reduction in the number of employees due to religious holidays. To overcome these issues, both cafes implemented measures such as non-discriminatory selection, training periods, briefings, and work calendar adjustments. The conclusion of this study is that diversity in organizational management at Hili Café and Copa Café can improve productivity and service quality if managed well, although there are still challenges that need to be overcome to optimize the benefits of diversity.